(untitled) (Annals of Medical Research, 2021)
Aim: Warfarin has been used for protection from peripheral embolism in patients with atrial fibrillation (AF) and it has been shown that the direct oral anticoagulants are effective in protection against stroke as much as warfarin and cause lower bleeding complications. Our aim is to compare the efficacies of different anticoagulants in resolution of left atrial appendage thrombi.Materials and Methods: 264 patients were included in study. 39 patients had left atrial appendage thrombus; 17 patients underwent a repeat transesophageal echocardiography (TEE) after switching/administering an anticoagulant treatment regimen.Results: Thrombus was detected in 3 patients using apixaban, who were switched to dabigatran. Those patients were found to have thrombus resolution by the repeat TEE procedures. Of 5 patients using warfarin, 3 were switched to dabigatran, in one of whom thrombus resolution was not achieved. One patient continued warfarin with a target INR of 2.5-3.5 and a repeat TEE showed complete thrombus resolution. The remainder patient using warfarin was swithed to rivaroxaban, with complete thrombus resolution having been achieved. Two patients using edoxaban had their thrombi resolved by dabigatran. Seven patients were not receiving any anticoagulant regimen. Among these, warfarin was administered to 4 patients and apixaban to 2; repeat TEEs showed no thrombus. The remainder patient was administered low molecular weight heparin, and repeat TEE showed persistence of LAA thrombus.Conclusion: Irrespective of patients being anticoagulated, TEE should be planned before interventional procedures and cardioversion. If thrombus develops in a patient receiving anticoagulant treatment, switching to a different anticoagulant would be a logical option.